SOSIALISASI PENGEMBANGAN PROSES KOMINUSI KALKOPIRIT PADA PRODUKSI CUSO4 UNTUK INDUSTRI KECIL MENENGAH DI YOGYAKARTA - Prameswara, Gyan; Tyassena, Flaviana Yohanala Prista; Perkasa, Pandu Dwi Cahya (ABDIMAS ALTRUIS: Jurnal Pengabdian Kepada Masyarakat, 2024)
The development of the mineral processing industry, especially chalcopyrite minerals, is increasing not only in large industries but also in small industries. Limited processing equipment and access to research and development results are still major obstacles for small industries to develop mineral processing businesses. This community service program (PKM) aims to be a bridge for the development of the chalcopyrite mineral processing business process (comminution process) in small industries to access related technology and knowledge. The optimum chalcopyrite comminution process to obtain a particle size of 180 μm was obtained using a 1-cycle jaw crusher (60% amplitude for 30 minutes) followed by grinding using a ball mill (25 rpm, 60 minutes using 20 balls). From the socialization results, it was also found that there was an increase in knowledge and capacity of PKM participants after socialization. The PKM participants' satisfaction with this program was also evaluated using a questionnaire, the survey results proved that this PKM had a positive impact on business processes in small industries.